History of the formation and development of the institution of custody on the Ukrainian territory (IXXVII centuries.) .: Historical and legal discourse - Uhach, Vasyl’; Kalaur, Lidia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The historical and legal aspects of the conception of the institution of custody and care on the territory of Ukraine are revealed. The national laws of the existence of this institute are distinguished both in the law based on customs and on regulatory foundation. In accordance with the feudal law, the origin of the legal norms of this institution, their influence on the formation of the legal system and the peculiarities of the implementation have been researched